2015
DOI: 10.1021/acs.analchem.5b00322
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Detection of Ricin Toxin in Multiple Sample Matrixes Using Single-Domain Antibodies

Abstract: Ricin is an extremely potent ribosomal inactivating protein listed as a Category B select agent. Although ricin intoxication is not transmittable from person to person, even a single ricin molecule can lead to cell necrosis because it inactivates 1500 ribosomes/min. Since there is currently no vaccine or therapeutic treatment for ricin intoxication, ultrasensitive analytical assays capable of detecting ricin in a variety of matrixes are urgently needed to limit exposure to individuals as well as communities. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 31 publications
1
43
0
2
Order By: Relevance
“…Various ELISAs have been developed by different groups [ 70 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 ]. Only a few of them are able to quantify ricin with detection limits down to a few pg/mL with limits of detection of 10 fg/mL [ 84 ], 2 pg/mL [ 70 ], 8 pg/mL [ 85 ], and 40 pg/mL [ 86 ]. Several ricin-specific ELISAs developed in different laboratories have been evaluated in a common ricin proficiency test panel organized in the framework of the EQuATox project, and results are presented in different manuscripts in this special issue of Toxins [ 42 , 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…Various ELISAs have been developed by different groups [ 70 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 ]. Only a few of them are able to quantify ricin with detection limits down to a few pg/mL with limits of detection of 10 fg/mL [ 84 ], 2 pg/mL [ 70 ], 8 pg/mL [ 85 ], and 40 pg/mL [ 86 ]. Several ricin-specific ELISAs developed in different laboratories have been evaluated in a common ricin proficiency test panel organized in the framework of the EQuATox project, and results are presented in different manuscripts in this special issue of Toxins [ 42 , 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is achieved by using antibodymodified magnetic beads that capture the analyte in solution, followed by binding of asecondary antibody with biotin labels to which streptavidin-b-galactosidase conjugate is attached. TheW alt research group has demonstrated the power of this technique for awide range of assays such as the cancer biomarker prostate-specific antigen, [43] the toxin ricin, [44] cytokines, [45] dengue fever, [46] and bacterial genomic DNA. We refer to this assay format as wide-field sampling/near-field detection measurements.T he detection limits achieved are exquisite:f or biotin-streptavidin it was 350 zm, which is equivalent to 10-20 enzyme labels in a100 mL sample.…”
Section: Wide-field Sampling/near-field Detectionmentioning
confidence: 99%
“…For screening purposes, mostly sandwich enzymelinked immunosorbent assays (ELISAs) are being used, detecting the presence of the protein and reaching detection limits from ng/mL to fg/mL depending on the antibodies and the read-out system used [19], where ultrasensitive detection has been obtained by using the proprietary single molecule array technology [20]. A less sensitive, but much faster approach is on-site detection assays such as lateral flow assays (LFA) or biosensor approaches based on different principles and read-outs that usually reach detection limits in the ng/mL range within about 30 min [15].…”
Section: Ricin From Ricinus Communismentioning
confidence: 99%